1989
DOI: 10.1172/jci114287
|View full text |Cite
|
Sign up to set email alerts
|

A nonsense mutation in the apolipoprotein C-IIPadova gene in a patient with apolipoprotein C-II deficiency.

Abstract: The apo C-II gene from a patient with apo C-1I deficiency has been sequenced after amplification by the polymerase chain reaction. A substitution of an adenosine for a guanosine at position 3002 in exon 3 of the patient's gene was identified by sequence analysis. This mutation leads to the introduction of a premature termination codon (TAA) at a position corresponding to amino acid 37 of mature apo C-II and to the formation of a new Rsa I restriction enzyme site not present in the normal apo C-II gene. Amplifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
21
0

Year Published

1990
1990
2013
2013

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(22 citation statements)
references
References 30 publications
1
21
0
Order By: Relevance
“…Nonsense mutations have sometimes been associated with lack of mRNA and protein, as in human f3-globin (34), human a I-antitrypsin (35), and insulin receptor (36) genes, while in other cases such as that of the LDL receptor or the apolipoprotein C-II genes a stable truncated protein is synthesized (37,39). It has been suggested that mRNAs presenting translation termination mutations might be unstable since they may not be protected by ribosomes from the endogenous RNAase digestion (34).…”
Section: Discussionmentioning
confidence: 99%
“…Nonsense mutations have sometimes been associated with lack of mRNA and protein, as in human f3-globin (34), human a I-antitrypsin (35), and insulin receptor (36) genes, while in other cases such as that of the LDL receptor or the apolipoprotein C-II genes a stable truncated protein is synthesized (37,39). It has been suggested that mRNAs presenting translation termination mutations might be unstable since they may not be protected by ribosomes from the endogenous RNAase digestion (34).…”
Section: Discussionmentioning
confidence: 99%
“…Normal levels of mRNA have been shown for the LDL receptor (36), for the beta-globin chain (37) and for apolipoprotein CII (38) in patients with nonsense mutations of these genes. Similar findings were reported for the dihydrofolate reductase gene in which nonsense mutations were artificially introduced at various points in the gene sequence (39).…”
Section: Discussionmentioning
confidence: 99%
“…Two additional CF patients, homozygous for the G542X nonsense mutation in exon 11, have been reported with similar clinical manifestations (12,13). Nonsense mutations in several human disease genes have been shown to cause severe reduction in mRNA levels, leading to absent protein product and severe clinical disease (14)(15)(16)(17)(18)(19)(20)(21)(22) 21 ( 11). She has very mild pulmonary disease for her age and severe pancreatic disease which have been fully described previously (1 1).…”
Section: Introductionmentioning
confidence: 99%